Report of negative results to Trichinella spp. by artificial digestion in domestic pigs of the lower valley of the Negro River, Argentine Patagonia (FAVE Sección Ciencias Veterinarias, 2020)
Currently, the Trichinella genus consists of 10 species and 3 genotypes. Transmission occurs only through ingestion of infected muscle tissue. Between the potential hosts there is a domestic cycle and a wild cycle with possible constant feedback between both. Since 2017, the operation of the San Javier Social Slaughterhouse, in the lower valley of the Río Negro, allows producers to access a safe operation that also provides guarantees to the consumer. The aim of the present study was to evaluate the presence of L1 larvae larvae of Trichinella spp. in domestic pigs from small and medium-scale farms. 10 grams of diaphragm from each domestic pig were analyzed by the artificial digestion method, forming pools of up to 10 animals. In total 942 domestic pigs were negative for the presence of L1 larvae of Trichinella spp. However, it should be borne in mind that production systems with the characteristics from which the analyzed animals come, would potentially be exposed to the feedback of Trichinella spp. from wildlife. Then, it is necessary to guarantee veterinary control in the slaughter of pigs and game prey and to support surveillance, updating and promotion actions in relation to the prevention of trichinellosis.
Keywords: Trichinellosis; domestic cycle; swine production; artificial digestion